Diagnosis and treatment of infantile malignant solid tumors in beijing, China: A multicenter 10‐year retrospective study - Jin, Mei; Tian, Zhi; Xie, Yao; Zhang, Zhaoxia; Li, Miao; Yu, Yaxiong; Zhang, Weiling; Zhao, Junyang; Wang, Huanmin; Zeng, Qi; Li, Long; Ge, Ming; et al. (Pediatric investigation, 2020)
Importance Cancer is the main cause of death by disease in children. Children experience the highest incidence of cancer in the first year of life. However, there is no comprehensive registration system for children with tumors in China. Objective To summarize the diagnosis and treatment of infant cancer and analyze the status of standardized diagnosis and management among several treatment centers in Beijing, China, thereby providing evidence to guide further clinical research. Methods From January 1, 2010 to December 31, 2019, patients with newly diagnosed infantile malignant solid tumors were admitted to six large tertiary pediatric solid tumor diagnosis and treatment centers in Beijing. The epidemiology, clinical features, and therapeutic effects of tumors in these patients were analyzed retrospectively. All patients were followed up until March 31, 2020. Results In total, 938 patients were enrolled in this study. There were 530 boys (56.5%) and 408 girls (43.5%); the median age was 6.0 months (range, 0–12.0 months). The three most common tumors were retinoblastoma in 366 patients (39.0%), neuroblastoma in 266 patients (28.4%), hepatoblastoma in 133 patients (14.2%), and central nervous system tumors in 52 patients (5.5%). The estimated 5‐year overall survival rate was 81.3% ± 1.8%, and the 5‐year event‐free survival rate was 71.8% ± 2.9%. The 5‐year overall survival rates of non‐rhabdomyosarcoma soft tissue sarcoma, neuroblastoma, and retinoblastoma were 100%, 88% ± 2.2%, and 86.9% ±2.1%, respectively. The 5‐year event‐free survival rates were 81.1% ± 2.7% for neuroblastoma, 81.6% ± 9.8% for non‐rhabdomyosarcoma soft tissue sarcoma, and 72.7% ± 14.1% for extracranial malignant germ cell tumors. Interpretation The three most common infantile malignant solid tumors were retinoblastoma, neuroblastoma, and hepatoblastoma. Multidisciplinary combined diagnosis and treatment is needed for infantile tumors. Children experience the highest incidence of cancer in the first year of life. We summarized 10‐years data of infantile malignant solid tumors from multiple centers in Beijing, China to provide evidence to support further clinical studies.